The gender earnings gap inside a Russian firm: first evidence from personnel data - 1997 to 2002 - Thomas Dohmen; Hartmut Lehmann; Anzelika Zaiceva (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2008)
Using unique personnel data from one Russian firm for the years 1997 to 2002 we study the size, development and determinants of the gender earnings gap in an internal labor market during late transition. The estimated gender earnings gap at the firm level falls from about 38 percent in 1997 to 18 percent in 2002. Gender earnings differentials are largest for production workers, who constitute the largest employee group in the firm. Various decompositions show that these differentials and their dynamics remain largely unexplained by observable characteristics at the mean and across the wage distribution. Our analysis also reveals that the earnings differentials for production workers largely stem from job assignment, as women are predominately assigned to lower-paid jobs. Earnings gaps within job levels are small and almost fully explained by observed characteristics. The convergence of male and female earnings is largely driven by an increase in the rewards for women, which is most pronounced in the lower part of the distribution.
Keywords: 330; Lohnunterschied; erwerbstätige Frauen; erwerbstätige Männer; geschlechtsspezifische Faktoren; Lohnentwicklung; Industriearbeiter; innerbetriebliche Hierarchie; Lohnstruktur; produzierendes Gewerbe; Maschinenbau; Großbetrieb; Russland